PENGARUH PEMBERIAN PENYULUHAN KESEHATAN MELALUI VIDEO ANIMASI TERHADAP PERILAKU SADARI - Rahmi Sari Kasoema Limidia Vidiandari (Universitas Fort de Kock Bukittinggi, 2022)
Women have the highest risk factors for breast cancer, according to data from the World Health Organization (WHO) about 95% of breast cancers occur in women until now realize is an effective way for early detection of breast cancer. This study aims to determine the effect of providing health education through animated videos on knowledge, attitudes and conscious actions in first-level students of the Faculty of Health, University of Fort De Kock Bukittinggi. This type of research is pre-experimental with a one group pre-test post-test design approach. This research has been conducted on November-December 2021 on first-year students of the Faculty of Health, University of Fort De Kock with a population of 282 people. Sampling using purposive sampling technique with a sample size of 74 people. Collecting data using a knowledge and attitude questionnaire sheet and a conscious action observation sheet. Data analysis includes univariate analysis and bivariate analysis using the Wilcoxon test. The results showed that the average knowledge about pre-test awareness was 6.378 and post-test knowledge was 13.64, the average pre-test attitude was 28.66 and post-test was 32.9, and the pre-test action average was 7.9 and post-test. 16.62. The results of the bivariate analysis showed that the provision of health education through animated videos had a significant effect on conscious knowledge (p = 0.000), attitudes (p = 0.000) and actions (p = 0.000). It was concluded that the provision of health education through animated videos had a significant effect on knowledge, attitudes and conscious actions in level I adolescent girls at the Faculty of Health, University of Fort De Kock. Therefore, it is expected that all parties can take advantage of animated video media in order to increase knowledge, attitudes and conscious actions in young women. Keywords : Counseling, Animated Video, Realize